Aplikasi Teknologi Tepat Guna pada Pembuatan Kue Donat, Kue Roti dan Roti Goreng pada Mitra Usaha Roti Sari dan Dian Jaya Kota Kupang - Muntasir, Muntasir; Prilmayanti, Sri (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
The application of appropriate technology in the form of electric stirrer and storefront of donut product storagehas been implemented appropriately and targeted to the business partner of Roti Sari and Dian Jaya Bakery Businesslocated in Kupang city. Until now the process of stirring, pengulenan or pengenyalan on household industry partners arestill done manually with simple equipment. In order to increase the added value and selling value of donut cake products,baking cookies, Bolu cake, it is necessary to synergy between universities with partners in the form of application ofappropriate technology for the development of science and technology. The method of this program is the provision ofmaterials, design and manufacture of tools, demonstration tools and equipment by the team, simulation tools, specialcounseling at the location of partners and suggestions as a follow-up in the endurance of production and assistanceactivities. This community service offering provides added value of production in terms of time and speed in massproduction, hygiene and clean. Increase the product value in quality or quality and quantity quantity is estimated from 3kg - 5 kg of raw material to 10 kg - 15 kg per cycle of production. Product demand increased after this activity. productionper day from 10 kg to 20 kg of wheat raw material after baking dough, processed, fried, sliced, and packed into 400 - 600donuts and fried bread Rp. 800 - 2,000.00 per seed. Interview results in partners explain this product in a day generaterevenue Rp. 600,000.00. Electrical stirrer and storefront of donut product storage help to overcome problems to partners